2018
DOI: 10.1007/s10113-018-1320-z
|View full text |Cite
|
Sign up to set email alerts
|

Water markets in federal countries: comparing coordination institutions in Australia, Spain and the Western USA

Abstract: Water markets are a prime example of decentralized resource allocation, yet their success often depends on strong coordination institutions, particularly as water is redistributed across sectors and political borders. The territorial division of authority in federal countries creates potential intergovernmental coordination challenges in river basins shared by multiple jurisdictions. This paper compares water markets and associated institutional reforms in Australia, Spain and the Western USA -three federation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
0
16
0
2
Order By: Relevance
“…A study comparing coordination institutions in Australia, Spain and the Western USA showed that all three countries have required capable coordination institutions to address the distributional conflicts associated with water markets. Coordination institutions can take multiple forms and include both formal and informal venues for planning, financing and conflict management matched to local conditions [23].…”
Section: Special Organizational Governancementioning
confidence: 99%
“…A study comparing coordination institutions in Australia, Spain and the Western USA showed that all three countries have required capable coordination institutions to address the distributional conflicts associated with water markets. Coordination institutions can take multiple forms and include both formal and informal venues for planning, financing and conflict management matched to local conditions [23].…”
Section: Special Organizational Governancementioning
confidence: 99%
“…The exclusion of key stakeholders can undermine accountability and legitimacy. Accountability mechanisms are particularly important for water reallocation in interstate river basins, as highlighted by Garrick et al (2018); accessible information on reallocation and its impacts on other national and local policy goals underpins the legitimacy of water markets.…”
Section: Governance Challengesmentioning
confidence: 99%
“…However, such local autonomy can also pose constraints on interstate coordination and accommodation of national interests, as exemplified by the comparison of reservoir operations policies in the USA and Canada (Benson 2018). Garrick et al (2018) start from a comparison of institutional arrangements to manage water trade in three federal countries (Australia, Spain and the USA). They find that effective interstate and centrallocal coordination is needed regardless of the level of decentralisation to deal with the distributional conflicts associated with reallocating water across political borders in interstate river basins.…”
Section: Governance Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Holistic approaches promoting efficient water allocation in water systems are needed (Cai, 2008;Lund et al, 2006). The need for appropriate water valuation is underscored by regulatory frameworks that promote economically efficient water allocation, for example, the Water Framework Directive (European Commission, 2000 in the European Union or the emergence of water markets in the western United States (Hadjigeorgalis, 2009;Hansen et al, 2014;Wheeler et al, 2017), Australia (Garrick et al, 2018;Lewis & Zheng, 2018;Owens, 2016;Wheeler et al, 2013), or the United Kingdom (Erfani et al, 2015;Parker, 2007).…”
Section: Introductionmentioning
confidence: 99%